THERMAL ENERGY CREATION AND HEAT CASTLING BETWEEN AN ELECTROCHEMICAL FOLLICLE AND ITS ATMOSPHERE - Qianfan Zhang (International Scientific and Current Research Conferences, 2021)
The theoretical formulation presented during this paper was developed to predict the follicle average temperature as a function of some time for a given follicle discharge current and its initial temperature under adiabatic and nonadiabatic conditions. The follicle average temperature versus time data calculated from the derived formulation is presented within the type of plots for an ideal lithium-based button follicle (for example, lithium(s)/electrolyte/carbon monofluoride(s)) during its discharge period. The presented data are briefly discussed in light of follicle component stability and safe discharge operation.